Analisis Faktor yang Berpengaruh terhadap Kelelahan Kerja pada Pekerja Rambut Palsu di CV. Dona Mandiri Cabang Lasiana Kota Kupang - Nadi Rispiandi Hauteas; Luh Putu Ruliati; Soni Doke (Universitas Nusa Cendana, 2019)
Work fatigue is one of the health problems that is often felt by workers, characterized by a decrease in efficiency and endurance at work. Many factors can affect the occurrence of work fatigue, that is worker factors, work factors and work environment factors. The specific purpose of this research is to analyze the influence of work period, sleep quality, breakfast habits, long hours of work and work room temperature on work fatigue of wig workers in CV. Dona Mandiri Kupang City Lasiana Branch. This type of research is analytic survey research and uses cross sectional research design. This research was conducted at CV. Dona Mandiri, Lasiana Branch, Kupang City, in July-August 2019. The populations in this study were all wig workers working at CV. Dona Mandiri Lasiana Branch in Kupang City, with a total sample of research using a total population of 61 respondents. Statistical tests using is simple linear regression analysis. Based on the results of the study, the significance and effect of working period shows (0.896 and 0.000); sleep quality (0.080 and 0.051); breakfast habits (0.001); work time (0.014) and temperature shows (0.003). It show that the variable working time does not have an effect on work fatigue, sleep quality variables does not have an effect on work fatigue, breakfast habits have an effect on work fatigue, the length of work variable has an effect on work fatigue and the temperature variable has an effect on work fatigue.